Basal Serum Cortisol Levels, Depression and Medial Temporal Lobe Atrophy in Patients with Mild Cognitive Impairment and Alzheimer’s Disease - Dhikav Vikas; Sharma Lokesh; Mishra Pinki; Sharma Neera; Singh Anand Kuljeet; Duraisamy Sharmila; Chandra Garga Umesh; Sethi Mansi (Journal of Depression And Therapy, 2016)
This clinical study explores associations among basal serum cortisol, depressive symptoms, and medial temporal lobe atrophy in patients with MCI and Alzheimer's disease. It discusses stress‑axis dysregulation as a potential contributor to neurodegeneration and outlines implications for assessment and intervention.
Keywords: Serum Cortisol